Proceedings of the Design Automation &Amp; Test in Europe Conference 2006
DOI: 10.1109/date.2006.244100
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Analysis of L2 Cache Elements to Single Event Upsets

Abstract: Memory elements are the most vulnerable system component to soft errors. Since memory elements in cache arrays consume a large fraction of the die in modern microprocessors, the probability of particle strikes in these elements is high and can significantly impact overall processor reliability. Previous work [2] has developed effective metrics to accurately measure the vulnerability of cache memory elements. Based on these metrics, we have developed a reliability-performance evaluation framework, which has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…The field analysis carried out in this work agrees with the findings presented in [12]. With the help of the MCA given in [17], it was observed that only 12% of the errors were found to have occurred in the LI cache.…”
Section: International Test Conferencesupporting
confidence: 89%
See 2 more Smart Citations
“…The field analysis carried out in this work agrees with the findings presented in [12]. With the help of the MCA given in [17], it was observed that only 12% of the errors were found to have occurred in the LI cache.…”
Section: International Test Conferencesupporting
confidence: 89%
“…As mentioned in [12], ECC protection reduces the effective vulnerability of the L2 data array to zero and the primary source of L2 vulnerability is the tag array. It was observed that the L2 tag vulnerability is greater than the vulnerability of LI data and Instruction cache for most of the SPEC benchmarks when a similar processor and memory organization was considered.…”
Section: International Test Conferencementioning
confidence: 99%
See 1 more Smart Citation
“…Due to their large share of the transistor budget and die area, on-chip caches suffer from an increasing vulnerability to soft errors [4]. As a critical requirement for reliable computing [5], protecting the information integrity in cache memories has captured a wealth of research efforts [5], [6], [7], [8], [9], [10], [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Such a study could provide enough insight into cache reliability behavior, which the designer could take advantage of to design highly costeffective reliable caches. Recent papers [8], [9], [10], [1], [15], [16] present some initial efforts toward such a cache vulnerability analysis. However, their cacheline-or wordbased vulnerability characterization used some simple generation model [17] that could not explore the temporal vulnerability of the cache, i.e., how different lifetime phases of the cache data contribute to vulnerability.…”
Section: Introductionmentioning
confidence: 99%